2018
DOI: 10.1111/cts.12585
|View full text |Cite
|
Sign up to set email alerts
|

Ceftazidime‐Avibactam Population Pharmacokinetic Modeling and Pharmacodynamic Target Attainment Across Adult Indications and Patient Subgroups

Abstract: Ceftazidime-avibactam is a novel β-lactam/β-lactamase inhibitor combination for the treatment of serious infections caused by resistant gram-negative pathogens. Population pharmacokinetic (PopPK) models were built to incorporate pharmacokinetic (PK) data from five phase III trials in patients with complicated intra-abdominal infection (cIAI), complicated urinary tract infection (cUTI), or nosocomial (including ventilator-associated) pneumonia. Ceftazidime and avibactam pharmacokinetics were well-described by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
114
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 77 publications
(125 citation statements)
references
References 44 publications
8
114
1
2
Order By: Relevance
“…The modeling is often performed in an iterative fashion as new data emerge, from initial dose selection to dose adjustment in important subpopulations through final dose justification and the establishment of in vitro susceptibility criteria (break points). [14][15][16][17][18][19] The overall methodological approach consists of 4 steps: (1) identification of appropriate pharmacokinetic/pharmacodynamic (PK/PD) targets from preclinical experiments (in vitro, in vivo) 15 ;…”
mentioning
confidence: 99%
“…The modeling is often performed in an iterative fashion as new data emerge, from initial dose selection to dose adjustment in important subpopulations through final dose justification and the establishment of in vitro susceptibility criteria (break points). [14][15][16][17][18][19] The overall methodological approach consists of 4 steps: (1) identification of appropriate pharmacokinetic/pharmacodynamic (PK/PD) targets from preclinical experiments (in vitro, in vivo) 15 ;…”
mentioning
confidence: 99%
“…The final model parameter estimates are shown in the Supplementary Materials. Prediction-corrected visual predictive checks confirmed that the various model iterations reflected the observed data [32,68]. These models were used in Monte Carlo simulations to support and Data sourced from study conducted by Flamm et al [57] validate dosage selection, with simulation methods summarized in the Supplementary Materials.…”
Section: In Vitro Interaction With Pulmonary Surfactantmentioning
confidence: 90%
“…The phase III trials all included sparse PK sampling schedules, and at various stages during the development program, additional patient PK and covariate data were incorporated into updated iterations of the ceftazidime and avibactam population PK models to evaluate the performance of the selected dose by assessing model predictions versus actual exposures. These analyses provided assurance that the selected regimen would provide adequate exposures for various clinically important patient subgroups, including patients with NP/VAP [31][32][33], and also supported selection of dosage adjustments for renal function [34,35]. In conjunction with microbiological surveillance data and data from in vitro and animal models, the simulations also supported determination of ceftazidime-avibactam MIC susceptibility breakpoints [36].…”
Section: Ceftazidime-avibactam: Development Overviewmentioning
confidence: 99%
See 2 more Smart Citations